THEORY AND PHILOSOPHY OF SCIENCE ISLAMIZATION - Ahmad Nabil Amir (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2023)
The paper discusses the rigorous framework of Islamization of knowledge, in light of its discursive philosophy and history and deep debates of Islamization of present-day knowledge. It looks into classical role of its major proponents and institutions in articulating the ideas of Islamization of knowledge and the essence of tawhid in late 1970-80s and its impact in spearheading the movement for dynamic and modern Islamic worldview and renewed religious consciousness. This was consistently undertaken by IIUM and IIIT in promoting the idea of Islamization of human knowledge and integration of knowledge and value. The study was qualitative in nature in the form of integrative library research. Data was collected from primary and secondary sources and analyzed using certain inductive and deductive method. The finding shows that fundamental issues in Islamization of knowledge has been articulated consistently with principal debate relating to classical ideas of its methodology and workplan